2021
DOI: 10.11604/pamj.2021.38.40.27309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of high risk human papilloma virus (HPV) genotypes associated with oropharyngeal cancers in a Nigerian population

Abstract: Introduction head and neck cancers have essentially been a disease of the elderly but recent studies are beginning to demonstrate their increasing incidence in young people with infections such as human papilloma virus (HPV). This study was carried out to determine the prevalence of high risk Human papilloma virus (hrHPV) related oropharyngeal carcinoma and its prevalent genotypes as well as their strength of association with HIV in adult Nigerian subjects. Methods this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Seven studies reported tobacco use in patients, which ranged from 20.0% to 66.8%. 18 , 19 , 40 , 41 , 46 , 48 , 57 Alcohol use was reported by five studies, ranging from 8.0% to 85.0%. 19 , 40 , 41 , 46 , 48 Sexual history was reported in two studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies reported tobacco use in patients, which ranged from 20.0% to 66.8%. 18 , 19 , 40 , 41 , 46 , 48 , 57 Alcohol use was reported by five studies, ranging from 8.0% to 85.0%. 19 , 40 , 41 , 46 , 48 Sexual history was reported in two studies.…”
Section: Resultsmentioning
confidence: 99%
“… 18 , 19 , 40 , 41 , 46 , 48 , 57 Alcohol use was reported by five studies, ranging from 8.0% to 85.0%. 19 , 40 , 41 , 46 , 48 Sexual history was reported in two studies. 40 , 41…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral cancer has diverse risk factors, and they include tobacco use [35][36][37], betel (areca) nut chewing [35], alcohol consumption [36], chronic occupational exposure to some petroleum-based and oxygenated solvents (e.g. tetrahydrofuran, diethyl ether and benzene) [38], viral infections (by human immunodeficiency virus (HIV), Epstein Barr virus, HPV) [35,[39][40][41], ultraviolet radiation [35,42] and undernutrition [43][44][45][46]. Of the diverse oral cancer risk factors, tobacco use, alcohol use and oral sex (a transmission route for HPV infection) are the three major risk factors of oral cancer globally [47,48].…”
Section: Major Oral Cancer Risk Factorsmentioning
confidence: 99%